Madrasah Head's Knowledge Management(Km) In Improving Communication Intelligence(Ci)In Mas Batamiyah Riau Islands Province - Muhammad Nasir; As’ad As’ad; Bahrul Ma’ani (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to determine and analyze the knowledge management (KM) practices of Madrasah Heads in improving Communication Intelligence (CI) in Batamiyah Private Madrasah Aliyah (MAS) Riau Islands Province. The research method used is a qualitative approach with a phenomenological case study type. The research population was three heads of MAS Batamiyah. This research uses field observation techniques with data analysis according to Miles and Huberman's theory. Data validity is tested based on the criteria of data trustworthiness, data transferability, data trustworthiness and data certainty. The research results show that the implementation of KM in improving CI has played a role in increasing CI through the effectiveness of management functions, namely (1) Planning, in the form of madrasah strategic policies in the form of preparing vision, mission, goals and programs as well as strategic plans with development through strengthening ECP and PAP, (2) Organizing, in the form of formalizing the duties and functions of managing private madrasah institutions; (3) Madrasah policy and action management strategies are carried out with a level of communication intelligence that is maximizing the effectiveness of motivation, optimizing the effectiveness of knowledge and optimizing the effectiveness of skills. The implementation of KM functions shows a management system in building CI which is seen from input, process, output and outcome which produces madrasah quality.